The Characteristics Of Muslimpreneurs From The View Of Muslim Scholars And Academician - Muhammad Ridhwan Ab. Aziz; Mohd. Faizal P.Rameli; Kalsom Ab. Wahab; Suhaida Mohd Amin (The International Institute Of Social And Economic Sciences, 2024)
IJoTE Vol. II / No. 2